Sustainable Symbiotic Relationship in The Human Ecosystem in The Development of Public Spaces (Case of Hanoi Historical Inner-City Area) - Doan Minh, Khoi; Pham, Viet Hong; Doan, Thu Minh (International Journal of Sustainable Construction Engineering and Technology, 2021)
In the last few years, the concept of the Human Ecosystem has been mentioned a lot frequently in Urban Environments related to social and natural ecosystems. The organization of public spaces cannot help but affect the relationships between human and natural ecology, economy, and culture. Perhaps the human activities have compromised the ecosystem so those relationships can be easily broken down. But it can also be enriched, or recovered from failures by establishing Symbiotic Relationships between natural, economic, and cultural elements in urban ecosystems. The research presents theoretical issues of Human Ecosystems in public space organization and specific applications in the case of Hanoi historical inner-city areas. It focuses on discussing theories of the structure and morphology of Human Ecosystems, the human behavior, the relationship between community behaviors, natural environment, and architecture of public spaces, to organize, enrich, and balance the service ecosystem of public spaces. These features are considered vital by the author in contributing to the preservation of natural resources, urban architectural heritage, creating architectural spaces and planning of public spaces towards ecological and green urban development.